Front Cover: Discovery of Benzo[d]imidazole‐6‐sulfonamides as Bromodomain and Extra‐Terminal Domain (BET) Inhibitors with Selectivity for the First Bromodomain (ChemMedChem 20/2022). (19th October 2022) - Cipriano, Alessandra; Milite, Ciro; Feoli, Alessandra; Viviano, Monica; Pepe, Giacomo; Campiglia, Pietro; Sarno, Giuliana; Picaud, Sarah; Imaide, Satomi; Makukhin, Nikolai; Filippakopoulos, Panagis; Ciulli, Alessio; et al.
Abstract : The Front Cover shows that compound 9a (in golden rod sticks), the benzimidazole bioisoster of azobenzene‐containing BET inhibitor MS436, preferentially binds to the first (BD1, in orange red) over the second (BD2, in slate blue) bromodomain of BET family members. In this study, bioisosteric replacement of the azobenzene moiety of selective BET inhibitors with a benzimidazole ring afforded a set of benzimidazole‐6‐sulfonamides. Evaluation of the binding activity against diverse BRD families endorses the benzimidazole as a useful scaffold to obtain compounds with improved selectivity towards the first bromodomains of BET family proteins. Cover design by Gianluca Sbardella. More information can be found in the Research Article by Alessandra Cipriano, Ciro Milite, Sabrina Castellano et al.